2015
DOI: 10.1371/journal.pone.0138247
|View full text |Cite|
|
Sign up to set email alerts
|

Whole Grain Intakes in the Diets Of Malaysian Children and Adolescents – Findings from the MyBreakfast Study

Abstract: BackgroundDiets rich in whole grain are associated with several health benefits. Little is known however, about whole grain consumption patterns in Malaysia. The aim of this study was to assess whole grain intakes and dietary source in Malaysian children and adolescents.MethodsThis analysis is from the MyBreakfast study, a national cross sectional study investigating eating habits among primary and secondary school children throughout Malaysia, conducted in 2013. Children (n = 5,165) and adolescents (n = 2,947… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 22 publications
4
28
0
Order By: Relevance
“…Consumption of whole grains was calculated at 21 g/d for adults (19-85 years) [9], indicating inadequate whole grain consumption. However, this was similar to the level of consumption recorded in the United Kingdom [10], the United States [11], Ireland [12] and Singapore [13], while other countries, such as France [14], Italy [15] and Malaysia [16] have far lower intakes. Scandinavian countries have recently increased intakes, in particular Denmark, where successful promotion of whole grains, via a public-private partnership, increased consumption from 33 g/day (from 2000 to 2004) to 55 g/day (in 2011-2014) [17].…”
Section: Introductionsupporting
confidence: 80%
“…Consumption of whole grains was calculated at 21 g/d for adults (19-85 years) [9], indicating inadequate whole grain consumption. However, this was similar to the level of consumption recorded in the United Kingdom [10], the United States [11], Ireland [12] and Singapore [13], while other countries, such as France [14], Italy [15] and Malaysia [16] have far lower intakes. Scandinavian countries have recently increased intakes, in particular Denmark, where successful promotion of whole grains, via a public-private partnership, increased consumption from 33 g/day (from 2000 to 2004) to 55 g/day (in 2011-2014) [17].…”
Section: Introductionsupporting
confidence: 80%
“…In theory, the combined effect of these components may be beneficial in preventing obesity. The weak association between Prudent diet and odds of overweight and obesity in the current study may be explained by the local dietary habits where whole grains were not commonly consumed among the Malaysian population [ 44 , 45 ]. Additionally, increased consumption of palm oil in the diet may contribute to the high-calorie intake among Malaysians [ 46 ].…”
Section: Discussionmentioning
confidence: 98%
“…Outcomes from the GReat-Child Trial indicated positive improvement in weight management [ 8 ], knowledge, attitudes, and practices toward whole grain [ 21 ], as well as whole grain intake and quality of diet among the children participants. Considering that whole grain intake among Malaysian children has been a mere 2.3 g/d [ 30 ] in the past few years, these positive findings may have significant impact on the long-term dietary habits among Malaysian children. To our knowledge, this is the first reported quasi-experimental trial designed to increase the whole grain consumption, as well as improve the overall quality of diet in Malaysian children who are overweight and obese.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, an earlier intervention aimed at improving the consumption of fruits among schoolchildren showed a result similar to our T1 results not being sustained at T2 [ 41 ]. It should be noted that whole grain foods are not only less available but also more expensive in Malaysia [ 30 ]. Whole grain foods availability and accessibility in the marketplace hinges on consumer demand along with cost, as well as the industry’s ability to produce whole grain foods and to maintain sufficient return on investment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation